The Role of Work Motivation, Competency, and Professionalism on Teacher Performance - Rahayu Mardikaningsih; Ella Anastasya Sinambela; Vatosoa Mendrika (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
One element of the school as a system is the teacher. The role of the teacher is one of the resources that determine the success of education, especially in teaching and learning activities in schools. This study aims to discuss the role of work motivation, competence, and professionalism on teacher performance. This study uses a survey method with a correlational quantitative approach. The research location is in the School Cluster, Gempol District, Pasuruan Regency. Data were collected from all primary school teachers in the UPTD Education and Culture of Gempol District as many as 40 people. The data analysis used is multiple linear regression. The findings of this study indicate that there is a significant role of teacher motivation, competence and professionalism to shape teacher performance together. Motivation partially plays a significant role in shaping teacher performance. Competence partially provides a significant role in the ups and downs of teacher performance. The formation of teacher performance is based on the professionalism of the teacher.